2010
DOI: 10.3945/jn.109.112466
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Plasma Protein Supplements Prevent the Release of Mucosal Proinflammatory Mediators in Intestinal Inflammation in Rats

Abstract: Spray-dried plasma (SDP) is a complex mixture of active proteins that modulates the immune response of gut-associated lymphoid tissue. We examined whether SDP and Ig concentrate (IC) supplementation could modulate cytokine expression and inflammatory mediators in rats challenged with Staphylococcus aureus enterotoxin B (SEB). Wistar-Lewis rats were fed diets supplemented with SDP (8% wt:wt), IC (1.5% wt:wt), or milk proteins (control diet) from weaning (d 21) to d 34 after birth. On d 32 and 35, the rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
63
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 32 publications
(46 reference statements)
13
63
2
Order By: Relevance
“…SEB stimulates lymphocytes to secrete interferon-g and TNFa (37) and this is correlated with reduced tight-junction protein expression (21) and increased permeability (28) . In our model, SEB administration also increased the release of TNFa and interferon-g, IL-6 and leukotriene B 4 in both mucosa and PP (38) . In addition, the stimulation of mucosal GALT by SEB led the mucosal immune response to a T-helper 1 response, since IFN-g and TNFa enhanced activation and proliferation of T-helper 1 cells (39) .…”
Section: Fig 1 Characteristics Of the Staphylococcus Aureus Enterotmentioning
confidence: 80%
See 3 more Smart Citations
“…SEB stimulates lymphocytes to secrete interferon-g and TNFa (37) and this is correlated with reduced tight-junction protein expression (21) and increased permeability (28) . In our model, SEB administration also increased the release of TNFa and interferon-g, IL-6 and leukotriene B 4 in both mucosa and PP (38) . In addition, the stimulation of mucosal GALT by SEB led the mucosal immune response to a T-helper 1 response, since IFN-g and TNFa enhanced activation and proliferation of T-helper 1 cells (39) .…”
Section: Fig 1 Characteristics Of the Staphylococcus Aureus Enterotmentioning
confidence: 80%
“…In pigs challenged with E. coli K88, Bosi et al (49) observed that the expression of proinflammatory cytokines was lower in animals fed SDP. Results from our laboratory indicate that plasma supplements reduce the expression of mucosal pro-inflammatory cytokines (50,38) and the activation of T-helper subsets in the lamina propria and in the epithelium (32) . These effects on mucosal cytokine profile can explain the reduction of mucosal inflammation by plasma supplements and the preventive effects of SDP and IC on changes in the mucosal permeability (31) , tight-junctional protein expression (35) and nutrient absorption (36) following SEB administration.…”
Section: Fig 1 Characteristics Of the Staphylococcus Aureus Enterotmentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction and retrotranscription of RNA were carried out as previously described (21). Real-time PCR was determined using a template of cDNA in a 20-l reaction containing 0.2 mol/l of each primer and 2 SyBr GreenER SuperMix (Life Technologies).…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 99%